An innovative appendage invagination procedure to reduce thrombus formation – a numerical model. Issue 4 (12th March 2018) - Hazan, Ori; Sternik, Leonid; Waiss, Dar; Eldar, Michael; Hoffer, Oshrit; Goitein, Orly; Kuperstein, Rafael; Konen, Eli; Ovadia-Blechman, Zehava
Abstract: Invagination is an innovative technique for closing the left atrial appendage (LAA) to reduce the risk of thrombi formation. The influence of LAA invagination on the flow fields in the atria was investigated based on a computational fluid dynamics. The simulation results demonstrated that the novel invagination process can eliminate low velocities (blood stasis) and low shear rate and thus decrease the risk of thrombus formation during atrial fibrillation. This innovative technique may enhance the clinical treatment of patients with atrial fibrillation by improving the atrial flow field while lowering the risk of creating emboli.